(untitled) (Praxis Educativa, 2025)
The article describes the contributions that an Academic Division whose educational offering in science, technology, mathematics, engineering and health generates to the social well-being of communities of the Chontalpa region, Tabasco, Mexico. To this end, a qualitative, naturalistic case study was carried out in the Multidisciplinary Academic Division of Jalpa de Méndez, in which multiple informants were used (administrative staff, teachers and students), various data collection instruments were applied. It was discovered that the Academic Division studied executes an experiential educational methodology based on projects; Despite this, the impact that the projects have is not significant in the communities near the Campus. It is concluded that the Division under study has the potential to generate social well-being in the communities near the Campus to the extent that it can link the projects that its university community executes with the needs of the environment.